A Highly Efficient Phosphorescence/Fluorescence Supramolecular Switch Based on a Bromoisoquinoline Cascaded Assembly in Aqueous Solution - Dai, Xian‐Yin; Hu, Yu‐Yang; Sun, Yonghui; Huo, Man; Dong, Xiaoyun; Liu, Yu (Advanced science, 2022)
Despite ongoing research into photocontrolled supramolecular switches, reversible photoswitching between room‐temperature phosphorescence (RTP) and delayed fluorescence is rare in the aqueous phase. Herein, an efficient RTP‐fluorescence switch based on a cascaded supramolecular assembly is reported, which is constructed using a 6‐bromoisoquinoline derivative (G3), cucurbit[7]uril (CB[7]), sulfonatocalix[4]arene (SC4A4), and a photochromic spiropyran (SP) derivative. Benefiting from the confinement effect of CB[7], initial complexation with CB[7] arouses an emerging RTP signal at 540 nm for G3. This structure subsequently coassembles with amphiphilic SC4A4 to form tight spherical nanoparticles, thereby further facilitating RTP emission (≈12 times) in addition to a prolonged lifetime (i.e., 1.80 ms c.f., 50.1 µs). Interestingly, following cascaded assembly with a photocontrolled energy acceptor (i.e., SP), the efficient light‐driven RTP energy transfer occurs when SP is transformed to its fluorescent merocyanine (MC) state. Ultimately, this endows the final system with an excellent RTP–fluorescence photoswitching property accompanied by multicolor tunable long‐lived emission. Moreover, this switching process can be reversibly modulated over multiple cycles under alternating UV and visible photoirradiation. Finally, the prepared switch is successfully applied to photocontrolled multicolor cell labeling to offer a new approach for the design and fabrication of novel advanced light‐responsive RTP materials in aqueous environments. A highly reversible supramolecular photoswitch between room‐temperature phosphorescence (RTP) and delayed fluorescence is constructed. This photoswitch is based on a bromoisoquinoline cascaded assembly and is successfully prepared in the aqueous phase. It benefits from light‐driven supramolecular RTP energy transfer to exhibit multicolor tunable long‐lived emission, and is successfully applied to photocontrolled multicolor cell labeling.